Developing a knowledge base for crime prevention: lessons learned from the British experience. Issue 4 (November 2018) - Tilley, Nick; Laycock, Gloria
Abstract During the past 20 years, there have been several initiatives, led by the British government, to improve crime prevention by informing policy and practice with research. Two in particular stand out for the scale of the investment: The first was the establishment of the Crime Reduction Programme (CRP) in 1999. The CRP was supposed both to be based on what was already known from research and also to improve the evidence base and was scheduled to run for a decade. The CRP involved an unprecedented financial commitment to improving the knowledge base of crime prevention. The second was the establishment of the What Works Centre for Crime Reduction (WWCCR) in 2013. The WWCCR attempts both to distil findings from high quality research on what works in crime reduction in a form that would be readily accessible to and useable by decision-makers, and to encourage original research to improve the knowledge base. We touch more briefly also on the creation of the National Police Improvement Agency in 2007 and its successor body, the College of Policing in 2013. The core mission of both has been to professionalise policing (including police efforts to reduce crime) by making policing more evidence based, and the College of Policing has been home to WWCCR. This paper will provide a critical account of these major efforts to bring evidence to crime reduction and discuss lessons that can be learned from their experience.